Mechanism of recruiting Sec6/8 (exocyst) complex to the apical junctional complex during polarization of epithelial cells - Yeaman, Charles (2004)
Sec6/8 (exocyst) complex regulates vesicle delivery and polarized membrane growth in a variety of cells, but mechanisms regulating Sec6/8 localization are unknown. In epithelial cells, Sec6/8 complex is recruited to cell-cell contacts with a mixture of junctional proteins, but then sorts out to the apex of the lateral membrane with components of tight junction and nectin complexes. Sec6/8 complex fractionates in a high molecular mass complex with tight junction proteins and a portion of E-cadherin, and co-immunoprecipitates with cell surface-labeled E-cadherin and nectin-2α. Recruitment of Sec6/8 complex to cell-cell contacts can be achieved in fibroblasts when E-cadherin and nectin-2α are co-expressed. These results support a model in which localized recruitment of Sec6/8 complex to the plasma membrane by specific cell-cell adhesion complexes defines a site for vesicle delivery and polarized membrane growth during development of epithelial cell polarity.